From Crisis to Opportunity? Causes and Consequences of the Politicization of the CFSP on the Example of the Refugee Crisis (2015-2017) - Kizilkaya, Derya (2021)
The outbreak of the refugee crisis in 2015 has thrown the European Union off-balance, not only when it comes to Asylum and Migration policy, but also in the Common Foreign and Security Policy (CFSP). The massive influx of refugees has put a spotlight on the link between internal and external security as well as on the protection of the EU's external borders and thus also gave high political relevance to the CFSP. In response to these security challenges, the EU adopted a new EU Global Strategy in 2016 realigning the priorities and objectives of the CFSP and calling for reform and deeper integration. All these processes introduced a new political dynamic and public attention, culminating in the Politicization of the Common Foreign and Security Policy of the EU. This dissertation gives an overview of the current theories on the European Union's Politicization by analyzing its characteristics, mechanisms, and consequences. Subsequently, this theoretical framework of politicization literature will be applied to the Common Foreign and Policy. The case of the refugee crisis is used to elaborate its contribution to the Politicization of CFSP. Against the background of the growing ties between internal and external security, this dissertation argues that the migration crisis has led to polarizing conflicts between the member states and the political actors in foreign policy. However, other than what might be expected, it shows that this politicization has not hindered but supported further integration of the Common Foreign and Security Policy of the European Union.